Use of agroindustrial residues for producing enzymes by Bacillus subtilis E - Matos, Madyu; Pérez Hernández, Y.; Valdivia, Aymara; Ranilla, María; Rodríguez, Zoraya; Rubio, Yasmary; Díaz, A.; Jardines, Sonia; Camacho, C. (Cuban Journal of Agricultural Science, 2020)
Wheat bran, sugar cane bagasse, rice husk and corn stubble were evaluated as substrates for the production of endocellulases, endoxylanases and mannanase by Bacillus subtilis E44 during solid state fermentation (SSF). The SSF was carried out in 250 mL flasks with 1g of substrates, enriched with minimal salts medium, and incubated for 24 hours at 37 °C. The extraction of the enzymatic crude was carried out by the addition of 0.02 mol L-1 sodium phosphate buffer, pH 7.0 (1:10 w/v) in a shaker at 110 rpm for 30 min. Enzyme production was evaluated by measuring enzyme activities in the crude. Based on results, wheat bran, sugarcane bagasse and corn stubble can be used to produce endocellulase, endoxylanase and mannanase, while rice husk cannot be used to obtain endocellulase. Endoxylanase production was superior to the rest of the enzymes and the best inducer was wheat bran (25.08 IU.mL-1), followed by sugarcane bagasse (9.32 IU.mL-1). Rice husk and corn stubble showed values of 6.92 IU.mL-1 and 6.95 IU.mL-1, respectively. Results demonstrated the potential of wheat bran, sugarcane bagasse and corn stubble to produce endocellulase, endoxylanase and mannanase. Rice husk is not a good inducer to obtain endocellulase. Bacillus subtilis E44 demonstrated to be a better producer of endoxylanase enzymes than mannanase and endocellulase. Key words: endocellulases, endoxylanases, mannanases, solid state fermentation